2018
DOI: 10.1063/1.5011804
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and translational dynamics and their relation to hydrogen bond lifetimes in an ionic liquid by means of NMR relaxation time experiments and molecular dynamics simulation

Abstract: We report a concerted theoretical and experimental effort to determine the reorientational dynamics as well as hydrogen bond lifetimes for the doubly ionic hydrogen bond +OH⋯O− in the ionic liquid (2-hydroxyethyl)trimethylammonium bis(trifluoromethylsulfonyl)imide [Ch][NTf2] by using a combination of NMR relaxation time experiments, density functional theory (DFT) calculations, and molecular dynamics (MD) simulations. Due to fast proton exchange, the determination of rotational correlation times is challenging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 64 publications
0
17
0
1
Order By: Relevance
“…The diffusion coefficients of ions for the different Li salt concentrations are different as can be seen in Figures and S8–S10. In a series of previously published reports, diffusion of a number of ILs was studied together with some other macroscopic transport properties such as viscosity and ionic conductivity. In these studies, a unique diffusion coefficient for each ion has been obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion coefficients of ions for the different Li salt concentrations are different as can be seen in Figures and S8–S10. In a series of previously published reports, diffusion of a number of ILs was studied together with some other macroscopic transport properties such as viscosity and ionic conductivity. In these studies, a unique diffusion coefficient for each ion has been obtained.…”
Section: Resultsmentioning
confidence: 99%
“…For complex liquids with larger molecules, such as glycerol and n -propanol, the neutron experiments have indicated that the true molecular diffusive motion is a mixed translational–rotational–vibrational displacement . For (2-hydroxyethyl)­trimethylammonium bis­(trifluoromethylsulfonyl)­imide IL, the simulated correlation function comprises two independent domains: the short-time performance declines within the picosecond time interval determine re-orientational correlation times, while the long-range nanosecond interval is actually accredited to the translational diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ILs can be both high and low dielectric media, and therefore, the dielectric responses of the cations and anions in ILs may be critical to understanding the thermodynamic and electrochemical properties of IL-based materials. 60 Moreover, specific interactions such as hydrogen bonding and aromatic interaction often exist in ILs and are of particular importance in the physical properties of ILs, [77][78][79][80][81][82][83][84][85][86][87] thus allowing us to distinguish ILs from inorganic salts. Indeed, Dupont proposed that 1,3-dialkylimidazolium ILs are described as hydrogenbonded polymeric supramolecules.…”
Section: Role Of Ils As a Compound Between Small Ions And Uncharged S...mentioning
confidence: 99%
“…Moreover, specific interactions such as hydrogen bonding and aromatic interaction often exist in ILs and are of particular importance in the physical properties of ILs, 77–87 thus allowing us to distinguish ILs from inorganic salts. Indeed, Dupont proposed that 1,3‐dialkylimidazolium ILs are described as hydrogen‐bonded polymeric supramolecules 31 .…”
Section: Electric Polarization and Specific Interaction Of Ilsmentioning
confidence: 99%
“…Nilai konduktivitas panas yang dihasilkan berkisar antara 1,89 W/mK -3,61 W/mK (79; 165; 166; 174) Perhitungan Konduktivitas: Diketahui untuk persen massa 1,5% dan konduktifitas listrik 4,0, maka konduktivitas molar dapat ditentukan dengan persamaan : Bilangan transport merupakan fraksi dari arus total yang dibawa oleh ion jenis tertentu.untuk larutan dengan 2 jenis ion (178)(179)(180)(181), bilangan dengan I + merupakan arus kation, I adalah arus total yang melalui larutan, dan Iadalah arus anion. Dapat diasumsikan sebagai: I + + I -= I (179)(180)(181)(182)(183) Bilangan transport merupakan pembatas t o , namun untuk limit konsentrasi nol dari larutan elektrolit itu (184)(185)(186)(187)(188) . Arus yang berasal dari setiap jenis ion berhubungan dengan mobilitas ion.…”
Section: Hantaranunclassified